RESILIENCE OF CHRONICALLY ILL: A SCOPING REVIEW - Zelčāne, Elīna; Pipere, Anita (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
In the field of psychology resilience of the chronically ill has been studied mostly using quantitative research methods, but there are much fewer qualitative studies. This scoping review aims to collect definitions of resilience, find out, whether resilience development strategies are mentioned and what research approaches are used in qualitative studies about the resilience of the chronically ill. The review was conducted, following the 5-stage framework by Arksey and O’Malley, PRISMA guidelines, and searching in PubMed, PsychInfo, and Scopus databases. The main keywords (patients with chronic illness, resilience, strategies, qualitative studies) were selected according to the Participants/Concept/Context (PCC) framework, 21 articles were included in the review. Resilience mostly was defined as the ability to recover, return to normality, and adapt to new conditions after experiencing stress, illness, or other negative events. In several studies, other terms like coping, personal strength, self-management, and psychological growth were used instead. Lived experiences of the chronically ill show that resilience is not a stable ability, it changes over time. Resilience can be developed, using different strategies, such as having a positive mindset, learning new skills, accepting help, or promoting a healthy lifestyle. Qualitative content analysis and thematic analysis were the most often used research approaches in qualitative studies about the resilience of the chronically ill.